Changes of bioactive composition and concentration in loquat flower extracted with water/Chinese Baijiu. Issue 4 (April 2023) - Shen, Zhebin; Chen, Junwei; Zhu, Jieli; Yu, Haixia
Abstract: Loquat is a high-value fruit tree with medicine and fruit homology. Loquat flowers with special fragrance, strong cold resistance and rich in various bioactive components, are valuable agricultural auxiliary products and have been widely used for making floral teas and beverages in recent years. In this study, we found the concentration of active components increased from the floral buds to initial flowers along with flower development, the bioactives of initial flowers were the richest in four flowering stages, and loquat flowers contained major volatile components such as alcohols, aldehydes and esters, which are the source of fragrance. When extract with hot water, the most efficient method was 80 °C for 30 min or boiling water within 2 h. For Baijiu (56% Vol), the best solid-to-liquid ratio was 3:100 (Dry flower: Baijiu) in 6–12 h. Baijiu achieved higher bioactive content than water extraction, the amygdalin concentration in Baijiu reached 0.3 mg/mL.